Na vida ou na morte, nós temos que nos ajudar!: a experiência das famílias rurais que convivem com o câncer avançado - Begnini, Danusa (2015)
Cancer is a disease in advanced stages does not offer the possibility of healing to the sick. In this sense, care for the patient with advanced cancer is a major challenge for families. With regard to rural families, there are numerous special characteristics that differ from families residing in other contexts, such as the geographical distance of the municipalities reference to cancer treatment, the occupational exposure, among others. These factors emphasize the need of nursing to know and include the uniqueness of this population in their care. Therefore, to understand the experience of rural families facing advanced cancer, so it is visible the place that occupies the disease in their daily lives, the strategies used when faced with this situation and how it reorganizes up and behaves against the illness of one of its members to cancer, is critical. The aim of this study was to understand the experience of rural family that owns one of its members with advanced cancer. This is a descriptive qualitative, based on the theoretical framework of Symbolic Interaction. The study site corresponds to municipalities in the northern region of the state. The study subjects were 11 families, totaling 27 participants who had one of its members ill cancer at an advanced stage and residents in rural municipalities defined as field of study. The data collection took place from March period August 2014. The data collection instrument was a narrative interview and the family genogram. The materials arising from the narratives was analyzed with emphasis on content, as proposed by Lieblich, Tuval-Mashiach and Zilber (1998) and organized according to the international theoretical Model Family Management Style Framework. The survey was conducted after approval of the CEP-UFSM under the CAE number 28057814.2.0000.5346. From the data analysis, it can be said that the family defines the situation in which it is based on the meanings and has lived experiences with other diseases in the family. Similarly, dividing the condition of your family illness from the philosophy that elects in their family group and establishes the mutuality in their relations. The family also realizes the consequences of advanced cancer and has prospects for the future, they are positive or negative. It is expected that the results of this study will be disseminated to various fields in the nursing acts enabling professionals to reflect on their behavior and contributions as health professionals to families facing the disease process by advanced cancer to feel supported and cared.